Aspectos epidemiológicos da malária no Amazonas - Ferraroni, José João; Hayes, Jack (Acta Amazonica, 1979)
Overall rates of malaria for Amazonas have be dropping since 1973. An exception to this trend are the newly opened roads, BR-174 (Manaus/Boa Vista) and BR-319 (Manaus/Porto Velho). BR-174 has been an endemic focus of drug resistant falciparum malaria and the vector Anopheles darlingi exhibit behavior resistance to DDT. Since 1974 when the Hospital de Moléstias Tropicais de Manaus first opened, nearly all hospitalized cases of malaria have been treated at this facility. Malaria cases (out patients) as well as hospitalized cases were studied to determine the nature of malaria. Data is presented by species of Plasmodium, month, year and by age and sex. Data is also presented from the military Hospital. Individuals from BR-174 constitued over 65% of all malaria cases seen by the hospital. This study is important because of its implications for future development of the Amazon.